A Synthetic Approach for Hepta-Branched β-Cyclodextrins Bearing Heterogeneous Carbohydrate Residues at Their Primary Side via a One-Pot Process with a Simultaneous Click Chemistry Reaction - Oda, Yoshiki; Yamanoi, Takashi (Synlett, 2023)
In this study, a synthetic approach is reported for generating hepta-branched β-cyclodextrins (CDs) bearing heterogeneous carbohydrate residues at their primary side via a one-pot process with a simultaneous click chemistry reaction. The reactions were performed by reacting two or three different species of 2-propynylated glycosides with a hepta-azide functional β-CD at various reaction molar ratios. 2-Propynylated glycosides acted as heterogeneous carbohydrate sources embedded into a hepta-azide functional β-CD. The simultaneous click chemistry reactions generated several desired β-CD derivatives with varying densities of the heterogeneous carbohydrates in a one-pot process. The article describes the effects of the combination of 2-propynylated glycosides and the reaction molar ratios in the click chemistry reactions.
Keywords: cyclodextrin; click chemistry reaction; carbohydrate-branched cyclodextrin; heteroglycoconjugate; heterogeneous carbohydrate; simultaneous reaction